Liberalization of the European Union gas market What consequences for the contractual performance of Algeria? - Said BRIKA; Lamia ATI (Dirassat Journal Economic Issue, 2017)
The liberalization of the gas market in the European Union started in 1998 with the adoption of the first gas directive.In 2009, the market is fully liberalized and the consequences of this movement are already recovered. This study highlights the consequences of liberalization on the contractual mode second gas supplier to the EU, outside the region, which is Algeria, its contractual performance is affected by the changes that have been made on the main clauses defining long-term contracts. Wherever possible, a comparative analysis was made ​​with Sonatrach's main competitors in the European market: